Twenty-First Century Marianne Moore Essays from a Critical Renaissance (Modern and Contemporary Poetry and Poetics, 2018)
This collection represents the growing twenty-first-century critical engagement with Marianne Moore's poetry: a Moore renaissance that draws on expanded biographical and archival materials and new editions of her work. These essays by a lively group of established and emerging Moore scholars explore many new dimensions of Moore's poetry, including its intimate relationships with food, numbers, labor politics, Persian art, religious hermeneutics, and dance. They examine the impact of precursors and contemporaries on Moore's oeuvre, as well as her poetry's influence on subsequent generations of artists. The volume also sheds new light on Moore's editorial work and on her underappreciated post-World War II career as a cultural icon. The volume concludes with six brief scholarly memoirs on the evolution of Moore studies since the 1980s.